The Synergy between Pharmacological Regimens and Dermocosmetics and Its Impact on Adherence in Acne Treatment - Elena Araviiskaia; Alison Margaret Layton; Jose Luis López Estebaranz; Falk Ochsendorf; Giuseppe Micali (Hindawi Limited, 2022)
Background. Acne is the most common inflammatory skin disease in adolescence. It is also prevalent in adults, especially females. The disease has a considerable impact on health-related quality of life. Many studies have reported the negative impact of acne on patients due to skin disfigurement, ineffective treatment, and adverse effects of the treatment. Numerous factors contribute towards nonadherence to therapy. Summary. This review discusses the various factors that are related to treatment nonadherence such as ineffective therapy, adverse effects with topical pharmacotherapy such as skin irritation and erythema as well as patient-related factors such as lack of knowledge of disease and a poor patient-physician relationship. Various methods are being adopted to increase adherence to treatments. Increased adherence to acne therapy has been associated with the use of dermocosmetics, such as moisturizers and cleansers. Encouraging the use of dermocosmetics in synergy with pharmacological regimens could support improved treatment adherence resulting in better clinical outcomes for acne patients. Conclusion. Dermocosmetics as an adjunct to pharmacological regimens has the potential to improve clinical outcomes by increasing treatment adherence in patients with acne.